Morbidity Associated With Cesarean Delivery in the United States: Is Placenta Accreta an Increasingly Important Contributor?. Issue 3 (September 2016) - Creanga, A.A.; Bateman, B.T.; Butwick, A.J.; Raleigh, L.; Maeda, A.; Kuklina, E.; Callaghan, W.M.
Abstract : ( Am J Obstet Gynecol. 2015;213(3):384.e1–e11) In the United States, 1.3 million women underwent cesarean delivery in 2012 alone. The fact that this is such a common surgery may have led to a heightened sense of safety surrounding the procedure despite the fact that it is associated with serious risks such as placenta accreta, which can result in major obstetric morbidity. The authors of this study investigated morbidity associated with both first and repeat cesarean deliveries with a special emphasis on placenta accreta. They also attempted to identify potential factors related to types of hospitals and patient demographics that might be associated with increased risk of such morbidity.